2015
DOI: 10.1016/j.jtcvs.2015.01.032
|View full text |Cite
|
Sign up to set email alerts
|

Pericardial diverticula misdiagnosed as pericardial cysts

Abstract: Pericardial cysts, which result from complete closure of an embryonic pericardial defect, are believed to occur at a frequency of 1 in 100,000, based on a 1958 chest radiograph screening. 1 Surgery is routinely not recommended, unless obvious compression of adjacent organs is demonstrated. However, 10% of all cysts may be instead a pericardial diverticulum with a persistent connection to the pericardial space, not apparent from radiologic studies, and identified only at surgery. 2 These lesions may cause atypi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Although radiologically a lesion may appear to be a pericardial cyst, in 10% of the time, it is actually a diverticulum 18 . Although dissimilar on anatomical basis, both pericardial cyst and diverticula are considered as a sequelae of common embryogenesis going wrong and are usually discussed together by most embryologists 18, 19, 20, 21, 22, 23, 24. Pericardial cysts and diverticula usually arise due to herniation through a structural defect in the pericardium 19, 20.…”
Section: Pericardial Cyst and Diverticulamentioning
confidence: 99%
See 4 more Smart Citations
“…Although radiologically a lesion may appear to be a pericardial cyst, in 10% of the time, it is actually a diverticulum 18 . Although dissimilar on anatomical basis, both pericardial cyst and diverticula are considered as a sequelae of common embryogenesis going wrong and are usually discussed together by most embryologists 18, 19, 20, 21, 22, 23, 24. Pericardial cysts and diverticula usually arise due to herniation through a structural defect in the pericardium 19, 20.…”
Section: Pericardial Cyst and Diverticulamentioning
confidence: 99%
“…Rohn et al first described similar origin of both the lesions and concluded that the pericardial cyst probably is a remnant of a diverticulum whose communication to the pericardial cavity has been obliterated 23 . To assure that it is truly a “cyst”, it might be necessary to trace the communicating channels during dissection of the pericardial cysts and if found be ligated to prevent a diverticulum from reoccurring 18 . Pericardial diverticula may be congenital or acquired.…”
Section: Pericardial Cyst and Diverticulamentioning
confidence: 99%
See 3 more Smart Citations